2016
DOI: 10.1080/02670836.2016.1152348
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, mechanical and bio-corrosion properties of Mg–Zn–Zr alloys with minor Ca addition

Abstract: In this research, effect of minor alloying element Ca on microstructure, mechanical and biocorrosion properties of as-cast Mg-3Zn-0.3Zr-xCa (x = 0, 0.3, 0.6, 0.9) alloys were investigated for biomedical application. The result showed that Ca played a dual role in mechanical properties and corrosion resistance. With minor Ca addition, the microstructure of the alloy is significantly refined and more uniform. The elongation, tensile strength and corrosion resistance of the studied alloys increases and then decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…1j. As demonstrated, MgZn 2 is the only intermetallic phase in Mg-Zn-Zr alloys [13] , whereas MgZn 2 and MgZnCu are two intermetallic phases in Mg-Zn-Zr-Cu alloys [14] . Therefore, the granular precipitates shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…1j. As demonstrated, MgZn 2 is the only intermetallic phase in Mg-Zn-Zr alloys [13] , whereas MgZn 2 and MgZnCu are two intermetallic phases in Mg-Zn-Zr-Cu alloys [14] . Therefore, the granular precipitates shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that Ca, a grain refining agent, enhances the strength of grain boundary by solid solution strengthening, and also due to the segregation of Ca at grain boundaries resulting in texture weakening and grain refinement. 13,36,52,78 It was observed that S2 composition had higher compressive strength values as compared to that of S1 composition, which could be attributed to the formation of higher intensity Mg-Ca phase. 67 Additionally, incorporation of Zn into the magnesium matrix, results into possible formation of ordered structure in the alloy system.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
“…12 Biodegradability in the scaffold material brings an added advantage that would avoid any revision surgery and associated complications. 13,14 Ceramics, metals, polymers and their composites have been traditionally used for fabricating bone scaffolds. Hydroxyapatite (HAp) and β-tricalcium phosphate (β-TCP), for example, are ceramic biomaterials which although possess bioactivity, are, not suitable for load-bearing applications due to their brittleness and low fracture toughness.…”
mentioning
confidence: 99%
See 2 more Smart Citations